IMPLEMENTASI PASAL 33 AYAT 3 UUD 1945 DALAM BERBAGAI PERUNDANG-UNDANGAN TENTANG SUMBERDAYA ALAM - Putra Astiti, Tjok Istri; Putri Kartika, Gusti Ayu; Ari Atu Dewi, Anak Agung Istri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015)DO - 10.24843/JMHU.2015.v04.i01.p05, 2015)
This study aims to : 1) determine the translation of Article 33, paragraph 3 of the 1945 Constitution in a variety of legislation on natural resources, 2 ) analyze the synchronization of several provisions in the legislation on the natural resources, espicially related to legal community participation and sanctions, and 3) analyze the implications of insynchroni- zation between the regulations of natural resource.                This research is a normative legal research is implemented using the statute approach. The main object of study is the primary legal materials in the form of legislation on natural resources.                The results showed that, in principle, the essence of Article 33 paragraph 3 of the 1945 Constitution, about the " earth , water , and space ,and the natural riches contained therein, shall be controlled by the state and used for the greatest welfare of the people . " has been translated into various statutory provisions of natural resources. There is synchronization between the various legislation, among other things : state control of natural resource management authorizes local governments, and the types of sanctions imposed against  violations to the various regulations, namely sanction of imprisonment, confinement and fine. However, there is not synchronization related to the delivery of state control of the rights to the indigenous people (legal community)and about magnitude of sanctions, there are countless monthly ,there are countless decades. Likewise, regarding the fine penalties, there is a very lightweight ( Rp 10,000 ) some are up to Rp 15.000.000.000,- The existence of the insynchronization may be implicated on the participation of the legal community (indigeneus people) in managing the local natural  resources and lack of legal positiveness (kepastian hukum)  in law enforcement for violations of the various regulations on these resources .
Keywords: Implementation, 1945 Constitution, Natural resource